Peningkatan Kompetensi Guru Sekolah Muhammadiyah di Surakarta melalui Pelatihan dan Pendampingan Penelitian Tindakan Kelas (PTK) - Achmad, Alfian; Maksum, Muh Nur Rochim; Wachidi; Hafidz; Mustofa, Triono Ali; Muthoharun Jinan; Istanto; Abidin, Zaenal (Abdi Psikonomi, 2024)
This community service activity was motivated by the fact that Muhammadiyah Elementary/MI, SMP, and SMK/SMA teachers in Kartasura did not fully understand PTK. The aim of this community service is that it is hoped that: Elementary/MI/SMP/SMA/SMK Muhammadiyah teachers in Kartasura have the knowledge, skills, values, and attitudes in making PTK proposals, formulating problems, looking for a theoretical basis, collecting data, analyzing data, making PTK reports, and able to submit articles to accredited national journals. This community service is carried out using the approach: (1) Lecture; (2) Discussion; (3) Questions and Answers; (4 Tasks; (5) FGD (Forum Group Discussion). Participants in this training and mentoring are 30 teachers from SD/MI, SMP, and SMA/SMK Muhammadiyah in Kartasura. The place for PTK mentoring and training is in the Muhammadiyah University Postgraduate Building Surakarta. Follow-up training and mentoring PTK teachers were divided into three groups, namely the SD/MI teacher group; (2) the Middle School teacher group, and (3) the SMA/SMK teacher group. Each group made proposals and carried out research. The results of PTK training and mentoring are (1) PTK reports; and (3) Articles submitted to accredited national journals.